Impact of a youth-led social marketing intervention run by adolescents to encourage healthy lifestyles among younger school peers (EYTO-Kids project): a parallel-cluster randomised controlled pilot study. Issue 4 (25th January 2019) - Tarro, Lucia; Llauradó, Elisabet; Aceves-Martins, Magaly; Moriña, David; Papell-Garcia, Ignasi; Arola, Lluis; Giralt, Montse; Solà, Rosa
Abstract : Background: Encouraging healthy lifestyles in children is a challenge. This project aimed to improve lifestyles of younger peers by engaging adolescent creators (ACs) to design and implement peer-led and social marketing (SM) health-promoting activities. Methods: A 10-month parallel-cluster randomised controlled school-based pilot study was performed in disadvantaged neighbourhoods in Reus (Spain) spanning two academic years (2015–2016/2016–2017). Eight primary schools (n=375 children) and four high schools (n=94ACs) were randomly placed in the intervention group. The 94 ACs (12–14 years) designed and implemented four SM activities for their younger peers (9–11 years). Eight primary schools (n=327 children) and three high schools (n=98 adolescents) served as the control group and received no intervention. Primary (physical activity and fruit consumption) and secondary outcomes (screen time, vegetables, soft drinks, sweets and fast food consumptions) were assessed with validated questionnaires at baseline and at the end of the study. Results: After 10 months, fruit consumption and physical activity were maintained in the children who consumed ≥1 fruit/day and spent ≥6 hours/week physical activity. However, compared with the controls, the intervention significantly increased the physical activity of girls to 15.6 min/week, whereas the percentage of girls who consumed sweets, soft drinks and fast food decreased significantly by 8.4%, 14.5% and 5.9%, respectively. Additionally, the percentage of ≥2 hour/weekday of screen time by boys decreased significantly by 8.2%. Conclusion: The European Youth Tackling Obesity-Kids, SM and peer-led intervention, effectively increased physical activity hours/week in girls, but was not effective in improving the percentage of children who consumed the recommended fruit. Moreover, the percentages of girls who consumed sweets, soft drinks and fast food and boys screen time decreased. Trial registration number: NCT02702336 ; Pre-results.